2004
DOI: 10.1016/j.bios.2004.02.006
|View full text |Cite
|
Sign up to set email alerts
|

CMOS microelectrode array for the monitoring of electrogenic cells

Abstract: Signal degradation and an array size dictated by the number of available interconnects are the two main limitations inherent to standalone microelectrode arrays (MEAs). A new biochip consisting of an array of microelectrodes with fully-integrated analog and digital circuitry realized in an industrial CMOS process addresses these issues. The device is capable of on-chip signal filtering for improved signal-to-noise ratio (SNR), on-chip analog and digital conversion, and multiplexing, thereby facilitating simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(101 citation statements)
references
References 48 publications
1
98
0
1
Order By: Relevance
“…Microscopic roughness can cause this effect [99,100], but a convincing review by Pajkossy [101] suggests that microscopic chemical inhomogeneities and ion adsorption play an even larger role (supported by data in [102][103][104]). Jorcin demonstrated that both surface effects and inhomogeneous current distribution contribute to CPE behavior [105].…”
Section: Constant Phase Elementmentioning
confidence: 99%
“…Microscopic roughness can cause this effect [99,100], but a convincing review by Pajkossy [101] suggests that microscopic chemical inhomogeneities and ion adsorption play an even larger role (supported by data in [102][103][104]). Jorcin demonstrated that both surface effects and inhomogeneous current distribution contribute to CPE behavior [105].…”
Section: Constant Phase Elementmentioning
confidence: 99%
“…Multi-site analysis of tissue is one of the most common applications for MEAs in vitro. Application of MEAs to record heart tissue [8,9] as well as neuronal network 35 behavior [10,11] is commonly done in various types of in vitro and in vivo preparations. Advantages are the good spatial resolution in combination with a high temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient flow was set at 50 μL·min −1 and at 100 μL·min −1 for drug delivery experiment done with the upper hole and lower hole, respectively. Fluorescence intensities for both experiments cannot be directly compared owing to photobleaching as a consequence of intermediary observation with a fluorescence microscope In our first CMOS design, (Heer, et al, 2004) we used an array of 4 × 4 electrodes, where each electrode has an associated unit of circuitry which filters and amplifies the recorded electrical signal. Additionally, each electrode can be used to apply electrical stimuli to the cellular culture to elicit an action potential.…”
Section: Resultsmentioning
confidence: 99%
“…A reactive-ion etch (RIE) is then used to open the nitride stack defining the size and shape of the electrodes. Detailed information regarding the design of the electronic circuitry was published previously (Heer et al, 2004).…”
Section: Electrode Designmentioning
confidence: 99%